If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 = 3(p + -5) Reorder the terms: 17 = 3(-5 + p) 17 = (-5 * 3 + p * 3) 17 = (-15 + 3p) Solving 17 = -15 + 3p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-3p' to each side of the equation. 17 + -3p = -15 + 3p + -3p Combine like terms: 3p + -3p = 0 17 + -3p = -15 + 0 17 + -3p = -15 Add '-17' to each side of the equation. 17 + -17 + -3p = -15 + -17 Combine like terms: 17 + -17 = 0 0 + -3p = -15 + -17 -3p = -15 + -17 Combine like terms: -15 + -17 = -32 -3p = -32 Divide each side by '-3'. p = 10.66666667 Simplifying p = 10.66666667
| 2y+4x=8x+-2 | | 2x/x+4=8/9 | | 2x+7=3x+4 | | 23+4x= | | 52=2x+y | | 7+4x=2x-11 | | 4/5=x/50 | | (2a)/3=-4.54545454545 | | 0.14(y-9)+0.10y=0.4y-0.01(60) | | 10-(-10)-7-5= | | 2c=5c+-19 | | 2(n+9)=3n-5 | | -3(7-4)= | | -3(7-4)= | | 5x+19+74= | | 9-y^2=14x+3 | | 6(9x-8)=47 | | d-17=45 | | -38+3r=8(4r+7)-7 | | 4x-9=7+9x+19 | | -32=-3+7x+3(x-2) | | -5x+7+3x=-1 | | 2(x-3)=5(2x+4) | | b+5=5/11 | | -x-47=31-7x | | 1.2b-1.8=47.4 | | 2a/3+5=5/11 | | 10-(3y-3)=8-4y | | 6.8x-4.7=-17.62 | | -7+4x+4x=-7 | | 11(t-2)+3t=7(2t+5)-10 | | 4/3(8x-3)=16 |